CONTRIBUTION TO THE STANDARDIZATION TRADITIONAL PRODUCTS ANDINOS : MACA , KIWICHA , CAÑIHUA , MASHUA. - Chasquibol-Silva, N. (1999)
4 varieties of Andean products are studied , considering the major producing regions and months of increased production, selected two varieties of maca , 3 quiwicha , one and one cailihua mashua . The applied chemical analyzes were based on standard methods of the AOC . Quantitative analyzes show the presence of mineral macronutrients ( Ca , P , K, Mg) , micronutrients essential biochemical processes (Mn , Zn , Fe) and primary metabolites (proteins ) . While in the qualitative analysis of important secondary metabolites such as amino acids , tannins and flavonoids appear .